Estimated glomerular filtration rate as one of the main predictors of in-hospital mortality in Egyptian patients with ST elevation myocardial infarction: a two-year retrospective study - Moheb Wadie; Emad Samaan; Mohammed Kamal Nassar; Mostafa Abdelsalam (The Egyptian Heart Journal, 2020)
Abstract Background Renal dysfunction is one of the major causes of in-hospital mortality in STEMI patients. In this study, we evaluated the combined predictive value of eGFR by CKD-EPI equation and shock index for in-hospital mortality and other adverse clinical outcomes in Egyptian patients with STEMI. Results A total of 450 STEMI patients were divided into 2 groups according to their eGFR with a cutoff value of 60 ml/min/1.73 m2 and compared as regards mortality, major bleeding, reinfarction, development of heart failure, stroke, and atrial fibrillation during the period of admission. Univariate analysis was performed to define significant factors that affected mortality; then, significant factors were subjected to a multivariate logistic regression. Patients with eGFR < 60 ml/min/1.73 m2 had higher rates of mortality (P  < 0.0005) and atrial fibrillation (P  =  .006) during the hospital admission. A multivariate logistic regression model showed the predictors of mortality were factors SI (OR = 28.56, 95% CI 8–101.97, P < 0.0001), cardiac troponin (OR = 2.89, 95% CI 1.08–7.77, P = 0.03), age (OR = 1.07, 95% CI 1.02–1.2, P = 0.002), and eGFR (OR = 0.98, 95% CI 0.96–0.99, P = 0.04). Conclusions Estimated GFR < 60 ml/min/1.73 m2 in STEMI patients is associated with higher rate of mortality. Estimated GFR, age, shock index, and cardiac troponin were the most significant predictors of mortality in STEMI patients